2005
DOI: 10.1074/jbc.m412850200
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal and Mitochondrial Oxidation of Fatty Acids in the Heart, Assessed from the 13C Labeling of Malonyl-CoA and the Acetyl Moiety of Citrate

Abstract: We previously showed that a fraction of the acetyls used to synthesize malonyl-CoA in rat heart derives from partial peroxisomal oxidation of very long and long-chain fatty acids. The 13 C labeling ratio (malonylCoA)/(acetyl moiety of citrate) was >1.0 with 13 C-fatty acids, which yields [13 C]acetyl-CoA in both mitochondria and peroxisomes and < 1.0 with substrates, which yields [13 C]acetyl-CoA only in mitochondria. In this study, we tested the influence of 13 C-fatty acid concentration and chain length on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…The labelling of the C1 + 2 moiety of BHB does not reflect that of the acetyl-CoA that enters the citric acid cycle. Our data also clearly demonstrate that octanoate can undergo two cycles of peroxisomal β-oxidation in liver, compared with one cycle in heart [31]. The relative labelling of the acetyl moiety of citrate and free acetate allows us to probe peroxisomal fatty acid oxidation in liver.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The labelling of the C1 + 2 moiety of BHB does not reflect that of the acetyl-CoA that enters the citric acid cycle. Our data also clearly demonstrate that octanoate can undergo two cycles of peroxisomal β-oxidation in liver, compared with one cycle in heart [31]. The relative labelling of the acetyl moiety of citrate and free acetate allows us to probe peroxisomal fatty acid oxidation in liver.…”
Section: Resultssupporting
confidence: 52%
“…This dilution results from the formation of unlabelled acetyl-CoA from the peroxisomal β-oxidation of unlabelled endogenous long-chain fatty acids. It thus appears that, although octanoate can undergo two cycles of peroxisomal β-oxidation in liver (compared with one cycle in heart [31]), a greater fraction of the first acetyl of octanoate undergoes peroxisomal β-oxidation compared with the second acetyl.…”
Section: Resultsmentioning
confidence: 99%
“…We showed that it is possible to estimate myocardial V TCA in vivo through the time-resolved 13 C MRS measurement of [5][6][7][8][9][10][11][12][13] C]citrate following the injection of hyperpolarized [1-13 C]acetate. V TCA and the dynamics of 13 C citrate labeling were independent on the amount of injected substrate and did not correlate with the dynamics of 13 C acetylcarnitine labeling.…”
Section: Resultsmentioning
confidence: 99%
“…The signal decay of precursor and metabolites results from a combination of the effects of longitudinal relaxation (characterized by the time constant T 1 ), RF excitation, and biochemical conversion and all time courses were corrected for the effect of repeated RF excitations. The T 1 of [1-13 C]acetylcarnitine was set to 14.9 s, as previously determined in vivo [35], and that of [5][6][7][8][9][10][11][12][13] C]citrate to 20 s [46]. The acetate signal decay was treated as free parameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation